Costunolide-Induced Apoptosis via Promoting the Reactive Oxygen Species and Inhibiting AKT/GSK3β Pathway and Activating Autophagy in Gastric Cancer - Xu, Cuixiang; Huang, Xiaoyan; Lei, Xiaohua; Jin, Zhankui; Wu, Min; Liu, Xiao; Huang, Yubin; Zhao, Xiangrong; Xiong, Yue; Sun, Jingying; Duan, Xianglong; Wang, Jianhua (Frontiers in Cell and Developmental Biology, 2021)
Objective: Costunolide (Cos) is a sesquiterpene lactone extracted from chicory. Although it possesses anti-tumour effects, the underlying molecular mechanism against gastric cancer cells remains unclear. This study aimed to explore the effect and potential mechanism of Cos on gastric cancer. Methods: The effect of Cos on HGC-27 and SNU-1 cells proliferation was analyzed by CCK-8 and clone formation assay. The changes in cell apoptosis were determined using Hoechst 33258 and tunel staining. The morphology of autophagy were observed by autophagosomes with electron microscope and LC3-immunofluorescence with confocal microscope. The related protein levels of cell cycle, apoptosis, autophagy and AKT/GSK3β pathway were determined by Western blot. The anti-tumour activity of Cos was evaluated by subcutaneously xenotransplanting HGC-27 cells into Balb/c nude mice. The Ki67 and P-AKT level were analysed by immunohistochemistry and apoptosis level was analyzed by tunel staining. Results: Cos significantly inhibited HGC-27 and SNU-1 cells growth, induced cell cycle arrest in the G2/M phase. And Cos activated intrinsic apoptosis and autophagy through promoting cellular ROS levels and inhibiting the ROS-AKT/GSK3β signaling pathway. Moreover, preincubating gastric carcinoma cells with 3-Methyladenine (3-MA), a cell-autophagy inhibitor, significantly alleviated the effects of Nar in promoting cell apoptosis. Conclusions: Cos induced apoptosis of gastric carcinoma cells via inhibiting the ROS-AKT/GSK3β pathway, and activating pro-death cell mitophagy, which may be an effective strategy to treat gastric cancer.